2015
DOI: 10.1159/000375118
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Contiguous Primary Hepatic Marginal Zone B-Cell Lymphoma and Hemangioma Ultimately Diagnosed Using Contrast-Enhanced Ultrasonography

Abstract: Primary hepatic marginal zone B-cell malignant lymphoma of mucosa-associated lymphoid tissue (MALT lymphoma) is extremely rare. We present a case in which a lesion was diagnosed as 2 contiguous tumors (MALT lymphoma and hemangioma) using contrast-enhanced ultrasonography (US) with sonazoid. There has been no previous case of contiguous hepatic MALT lymphoma and hemangioma. The present case was a female with no medical history. We detected a snowman-like appearance, which was a tumor of 15 mm in diameter with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 16 publications
2
18
0
Order By: Relevance
“…[22,24] Meanwhile, distinctive radiological features were absent. Ultrasound studies showed majority of the hepatic MALT lymphomas as hypoechoic masses, [7,15,16,22,26,29,31,40,43] which was in agreement with a previous study of liver lymphomas. [51] On contrast-enhanced CT, primary hepatic MALT lymphoma had been described as low-density mass, which was not enhanced, [16,17,31,39] or faint enhanced, [15,36,40] or enhanced peripherally in the early arterial phase.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…[22,24] Meanwhile, distinctive radiological features were absent. Ultrasound studies showed majority of the hepatic MALT lymphomas as hypoechoic masses, [7,15,16,22,26,29,31,40,43] which was in agreement with a previous study of liver lymphomas. [51] On contrast-enhanced CT, primary hepatic MALT lymphoma had been described as low-density mass, which was not enhanced, [16,17,31,39] or faint enhanced, [15,36,40] or enhanced peripherally in the early arterial phase.…”
Section: Discussionsupporting
confidence: 91%
“…Ultrasound studies showed majority of the hepatic MALT lymphomas as hypoechoic masses, [7,15,16,22,26,29,31,40,43] which was in agreement with a previous study of liver lymphomas. [51] On contrast-enhanced CT, primary hepatic MALT lymphoma had been described as low-density mass, which was not enhanced, [16,17,31,39] or faint enhanced, [15,36,40] or enhanced peripherally in the early arterial phase. [29] MRI was characterized by low signal intensity on T1-weighted images and moderately high signal intensity on T2-weighted images, and the enhancement pattern was similar to that of CT. [15,22,35,36,40,43] Our case also had these radiological features.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Lymphoma shows homogeneous hypoechogenicity on baseline US. On Sonazoid CEUS, lymphomas show early homogenous hyperenhancement and early wash-out in the vascular phase and defect in the postvascular phase [105].…”
Section: Lymphomamentioning
confidence: 99%
“…On CT scans, the hepatic MALT lymphoma is enhanced peripherally in the arterial phase and low attenuat- ed in the delayed phase, according to an earlier report (4). Another study indicated that hepatic MALT lymphoma shows prolonged enhancement in the delayed phase on dynamic CT and is enhanced in the arterial phase with persisting enhancement in the portal phase on dynamic MRI (9). Similarly, in our case, enhancement was evident in the arterial phase; however, unlike previous reports, our case showed iso-attenuation in the delayed phase and undistorted vessels traversing the liver mass (6).…”
Section: Index Termsmentioning
confidence: 80%